Bimbingan Teman Sebaya untuk Mencegahan Penyimpangan Seksual Siswa - Afrizal Afrizal; Reno Diqqi Alghzali (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The purpose of this study was to find out how the process of peer guidance and the results of peer guidance in preventing student sexual deviation. This type of research is field research that uses a qualitative descriptive approach method. From the results of research in the field, it is illustrated that the peer guidance process carried out at MAN Curup has been carried out by members of PIK-R Kasturi. The results of peer guidance activities carried out at MAN Curup in order to prevent free sex in MAN Curup. Guidance activities are carried out in accordance with what is planned or determined. MAN Curup students trust the guidance of their peers. Peer guidance in guiding strongly holds the principles and principles of guidance, and the time used in guiding can be adjusted to existing conditions, and from the implementation of peer guidance the results achieved are that most students understand and are able to apply what has been obtained from peer guidance.